Effect of Dietary Carbohydrate‐to‐lipid Ratios on Growth Performance, Body Composition, Hepatic Enzyme Activities, and Digestive Enzyme Activities of Juvenile Australian Redclaw Crayfish, Cherax quadricarinatus (von Martens). Issue 2 (3rd April 2013) - Zhu, Huanxi; Jiang, Qichen; Wang, Qing; Yang, Jianghua; Dong, Siming; Yang, Jiaxin
Abstract A growth experiment was conducted to determine the optimal dietary carbohydrate‐to‐lipid (CHO : L) ratio for the Australian redclaw crayfish, Cherax quadricarinatus (von Martens). Specimens were divided into five treatment groups and fed twice a day to apparent satiation with isonitrogenous and isoenergetic diets with dietary CHO : L ratios of 10.75:1, 5.99:1, 3.60:1, 2.18:1, or 1.33:1. Over the 8‐wk growth trial, redclaw crayfish fed the 2.81:1 and 3.60:1 diets exhibited better weight gain (WG), specific growth rate (SGR), and feed conversion ratio (FCR) than specimens fed the other diets (P < 0.05). Activities of hexokinase and pyruvate kinase were stimulated by elevated levels of dietary carbohydrate, whereas activities of lipase and alkaline phosphatase were stimulated by elevated levels of dietary lipid. Dietary CHO : L ratios significantly affected digestive enzyme activities (P < 0.05), except for trypsin (P > 0.05). On the basis of the analysis of growth, FCR, and costs of culturing redclaw crayfish, the optimal growth and costs occurred when the dietary carbohydrate and lipid levels were 290.10 g/kg and 80.70 g/kg, respectively, corresponding to a CHO : L ratio of 3.60:1. These results indicate that a CHO : L ratio of 3.60:1 is optimal for rearing redclaw crayfish and that this species uses carbohydrate more efficiently than lipid.